Characterization of membrane organization and dynamics in giant unilamellar vesicles assembled from rat kidney membrane extracts and fragments - Cheng, Melanie Anne B. (Ann Arbor Michigan ProQuest Information and Learning Company, 2006)
In renal proximal tubular cells, the plasma membrane is polarized in terms of composition, structure and function into distinct regions: the brushborder (BBM) and the basolateral (BLM) membrane. The purpose of our work is to gain insight into the complex structure of biological membranes by applying the techniques that have been used in characterizing artificial membrane systems to natural membranes reconstituted into giant unilamellar vesicles (GUVs). In GUVs made from natural lipid extracts from BBM and BLM, we observed phase separation through the formation of non-fluorescent domains at physiological temperatures, implying that domain formation may be driven by lipid-lipid interactions. In intact membrane GUVs, the morphology and membrane fluidity of the vesicles demonstrate that membrane proteins also play an important role in the organization of natural membranes. The presence of domains in these membrane preparations gives support to the presence of "rafts" or raft-like membrane domains in natural membranes. GUV studies of natural membranes would be incomplete without the determination that the membrane in the vesicles closely approximates the structure and composition of the plasma membrane. Thus the incorporation of proteins in the GUVs assembled from intact membrane fragments was confirmed through primary and secondary antibody detection of various membrane proteins: type IIa Na/Pi cotransporter (NaPi-IIa), beta-actin and Na+/K+ ATPase. Fluctuation correlation spectroscopy (FCS) measurements performed on the intact BBM reveal that the protein-lipid dynamics in renal BBM is complex with a large range of diffusing species. In particular, the dynamics of NaPi-IIa was related to the perturbations in the BBM as a result of dietary potassium deficiency. By calculating the diffusion coefficient of NaPi-IIa and using photon counting histogram (PCH) analysis to measure protein aggregation, we determined that the lateral diffusion of NaPi-IIa is slowed down and its aggregation is increased in potassium deficiency, both of which are associated with the decreased Na/Pi cotransport activity. This model was proposed as a means for posttranslational regulation of Na/Pi cotransport activity that is mediated by the increased sphingomyelin and glycosphingolipid content in potassium-deficient BBM, although the mechanisms by which these lipids may modulate NaPi-IIa activity have yet to be determined.--Abstract.
Thesis (Ph.D.)--University of Illinois at Urbana-Champaign, 2005.
Keywords: Biology, Cell